SERS platform for detection of lipids and disease markers prepared using modification of plasmonic-active gold gratings by lipophilic moieties; Sensors and Actuators B: Chemical; Vol. 265 - Guselnikova O. A. Olga Andreevna; Kalachyova E. Evgeniya; Grobonova K. Karolina; Trusova M. E. Marina Evgenievna; Barek J. Jiri; Postnikov P. S. Pavel Sergeevich; Svorcik V. Vaclav; Lyutakov O. Oleksy (2018, 2018)
Title screen